Knowledge Is (Still) Key: Awareness to Shape Trends in Telemedicine Use during the Pandemic Based on Management Perceptions and Implementation Systems - Nada I. Hawa; Tri E. B. Soesilo; Nuraeni Nuraeni (International Journal of Telemedicine and Applications)
Objectives. The digital revolution has brought rapid developments to the health sector. People were taking advantage of telemedicine technology during the COVID-19 pandemic. Telemedicine is highly recommended during a pandemic because it will reduce the transmission rate of viruses, and it is considered adequate and low-cost. However, a fundamental challenge still occurs; most people need to be used to telemedicine technology. Presumably, inadequate education and lack of experience regarding the use of telemedicine are obstacles for society in utilizing telemedicine. Methods. This study is aimed at determining the factors that influence the use of telemedicine. It focused on variables such as data confidentiality, administration, and knowledge to measure potential factors that pushed people to utilize telemedicine. We used a quantitative approach, using multivariate analysis, namely, simple linear regression. Most of our respondents are people aged 18-30 years young. Results. All respondents stated that administration factors in the implementation of telemedicine were good. Through the Chi-square test, the data safety factor has no effect (p value =0.090 or >0.05) on telemedicine implementation, while the knowledge factor has a significant effect on telemedicine implementation with a p value =0.043 (<0.005). The multivariate analysis explained that the knowledge variable influenced telemedicine use with a p value =0.033 (<0.05), meaning it contributed 1.624 times to telemedicine. Conclusion. This study discusses the factors that influence the use of telemedicine. The study’s results explain that the knowledge variable is the most significant factor influencing telemedicine use. Knowledge is an intellectual property that everyone must have to capitalize on with telemedicine. A lack of knowledge will become an information gap and a barrier for someone to reach new tools/technologies.